Tumor microenvironment responsive Mn-based nanoplatform activate cGAS-STING pathway combined with metabolic interference for enhanced anti-tumor therapy - E. Wen; Yu Tian; Yu Chen; Zhigang Wang; Yi Feng; Zhen Liao (Journal of Nanobiotechnology)
Abstract Despite the encouraging developments in tumor immunotherapy, the complex tumor microenvironment (TME) and abnormal energy metabolism persist as key factors facilitating immune escape. Recent research has emphasized the significant potential of the Manganese ions (Mn2+) as a “immune ion reactors” have the potential to stimulate cGAS-STING signaling pathway in modulating tumor immunotherapy. However, their efficacy is limited by insufficient targeting and lack of tumor specificity. To address these challenges, we have developed a nano-drug named as LT@MnO@MON-HA (LMMH), which incorporates manganese oxide (MnO) nanoparticles as the core and organic mesoporous silica as the outer layer. The mitochondrial glycolysis inhibitor lonidamine (LT) is encapsulated within the mesopores of LMMH and subsequently coated with hyaluronic acid to achieve precise tumor-targeted drug delivery. After reaching the tumor site, LMMH can decompose in the reducing and acidic TME, releasing LT and Mn2+. Once internalized by cells, LT rapidly localizes to mitochondria via functional groups, disrupting mitochondrial metabolism and increasing intracellular reactive oxygen species levels. Mn2+ catalyze the conversion of hydrogen peroxide (H₂O₂) into more cytotoxic hydroxyl radicals (·OH), thereby enhancing chemodynamic therapy (CDT). The mesoporous silica shell of LMMH is capable of depleting glutathione in the TME, enhancing CDT. Moreover, LMMH functions as an agonist of the cGAS-STING pathway, stimulating cytokine release and activating effector T cells, which in turn triggering systemic immune responses against primary and metastatic cancers. Collectively, these finding highlights the dual mechanisms by which LMMH enhances combination immunotherapy by regulating the TME and tumor metabolism. Graphical Abstract